Effects of water flow on ventilation rate and plasma cortisol in Nile tilapia introduced into novel environment - Roza e Silva, Maria Luiza [UNESP] (2020)
Water flow is a typical hydrodynamic variable of natural occurrence in fish's lifetime and understanding its impact on biological processes (e.g. stress) can contribute to improve welfare in captive/farmed fish. For that, we tested whether water flow is a stressor by itself in a non-rheophilic (i.e. theoretically sensitive to water flow) fish species: Nile tilapia (Oreochromis niloticus). Additionally, this species was chosen due to its importance for world aquaculture and because is cultivated in a number of systems which the water flow could potentially be a stressor such as indoor tanks, recirculating aquaculture systems, biofloc system and cages. Here, we exposed fish to a novel environment with (520 L h−1) or without a deliberated water flow, and we measured plasma cortisol and ventilation rate (VR) as indicators of stress. In a first experiment, the VR was reduced by flow immediately after tilapia transference to a novel environment (16 min of evaluation), but cortisol was not affected. The plasma cortisol levels were also measured in a second experiment, 30 min, 1, 2 and 4 h after transference to a novel environment, but was also not affected by the presence of flow. In a theoretical perspective, flow is not a stressor by itself in a non-rheophilic species. It acted as a hydrodynamic factor that decrease the magnitude of ventilation response in a fish introduced into a novel environment, without effects on plasma cortisol levels. Therefore, the water flow eventually can be used to assist fish oxygenation after a disturbance event, such as introduction into a novel environment.